Information Sharing, Informal Contracts, and Supply Chain Performance of SMEs in Gunung Kidul Regency, Indonesia - Yuli Liestyana; Hadi Oetomo; Tri Wahyuningsih; Muhamad Kiki Ariyanto (International Journal of Applied Business and International Management, 2022)
Supply chain performance refers to the activities to meet the end customer's requirements. This study aims to analyze the effect of information sharing and informal contracts on supply chain performance with trust as a mediating variable in silver-making SMEs in Pelemgede, Sodo, Paliyan, Gunung Kidul Regency, Special Region of Yogyakarta, Indonesia. Data were collected using a questionnaire. This study used PLS with SmartPLS 3.0 software to analyze the hypothesis. The findings indicate information sharing has a positive impact on trust. Also, trust positively impacts supply chain performance, trust mediates the impact of information sharing on supply chain performance, and the effects of informal contracts on supply chain performance. Advanced research can be done by applying the study in other SMEs fieldsÂ